Harnessing multi-doping porous carbon from Musa paradisiaca L. peel waste for solid-state supercapacitors - Purba, Cenora Evelynza; Nursyafni, Nursyafni; Apriwandi, Apriwandi; Kresna, Pharada; Julnaidi, Julnaidi; Nasir, Muhammad; Farma, Rakhmawati; Dewi, Rahmi; Martin, Awaludin; Hardanto, Lilik Tri; Taslim, Rika; Taer, Erman (Universitas Riau, 2024)
The demand for low-cost carbons with multi-doping in supercapacitors has led to a significant focus on utilizing biomass waste to produce activated carbons. The research successfully utilized Musa paradisiaca L. (MPL) peel as a porous carbon for solid-state supercapacitor. The process involved collecting banana peel waste, drying the peels using sunlight, pre-carbonization using a furnace, pH neutralization, drying, crushing carbon particles, and ensuring uniform particle size. Different concentrations of the catalytic ZnCl2 solution (300, 500, and 700 mmol/g) were selected to optimize physical and electrochemical properties. The resulting chemically activated MPL carbon powder was evaluated using SEM-EDS, XRD, and BET. MPL activated carbon with a 500 mmol/g solution of ZnCl2 was found to have optimal physical properties with a carbon percentage of 81.65%, oxygen 17.39%, phosphorus 0.42%, and boron 0.52%. Electrochemical properties were evaluated using dual-electrode system was exhibited the highest specific capacitance of 67 F/g. These findings demonstrate the potential of MPL peel waste as a high quality electrode for supercapaicor next-generation.